Tree species diversity and stand structural stability in secondary evergreen broadleaf forests of southern Vietnam - NGUYEN THI HA; TRAN THI NGOAN; DANG VIET HUNG; NGUYEN HONG HAI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ha NT, Ngoan TT, Hung DV, Hai NH. 2026. Tree species diversity and stand structural stability in secondary evergreen broadleaf forests of southern Vietnam. Biodiversitas 27 (2): d270209. https://doi.org/10.13057/biodiv/d270209. Species diversity and stand structural stability are fundamental concepts in ecology, yet their relationship remains debated. This study was conducted to evaluate the link between tree species diversity and stand structural stability of evergreen broadleaf forests in La Nga Protection Forest Management Board, Lam Dong Province, Vietnam. Data were collected from 102 temporary sample plots (500 m2 each) across three forest types: medium evergreen broadleaf forests (29 plots), poor evergreen broadleaf forests (33 plots), and woody-bamboo mixed forests (40 plots). The results identified a total of 128 species across the three forest types, with a moderate level of species similarity, as indicated by Jaccard indices ranging from 0.60 to 0.66. Species relationships showed an overall co-occurrence tendency across all forest types. Tree species diversity indices in the Evergreen Broadleaf Medium (EBM) Forests were higher than those in Evergreen Broadleaf Poor (EBP) and Woody-Bamboo Mixed (WBM) Forests, but the differences were not statistically significant (p > 0.05), except for the Pielou Index (p<0.05). Stand structural stability based on the Godron Index showed the ranking EBM > EBP > WBM among the studied forest types. Both Simpson (D) and Pielou (J’) Indices were positively correlated with stand structural stability (p < 0.05). These findings highlight the importance of conserving tree species diversity to maintain stand structural stability, while providing a scientific basis for the sustainable management of rehabilitated forest ecosystems in Vietnam.